Exercise haemodynamics may unmask the diagnosis of diastolic dysfunction among patients with pulmonary hypertension. (8th December 2014) - Maor, Elad; Grossman, Yoni; Balmor, Ronen Gingy; Segel, Michael; Fefer, Paul; Ben‐Zekry, Sagit; Buber, Jonathan; DiSegni, Elio; Guetta, Victor; Ben‐Dov, Issahar; Segev, Amit
<x xml:space="preserve">Abstract</x> Aims Heart failure with preserved ejection fraction can lead to pulmonary hypertension. The aim of the present study was to evaluate the role of exercise during right heart catheterization in the unmasking of diastolic dysfunction. Methods and results Between 2004 and 2012, 200 symptomatic patients with exertional dyspnoea, preserved left ventricular systolic function and suspected pulmonary hypertension, underwent right heart catheterization. Included in the study were 63 patients with resting pulmonary arterial wedge pressure (PAWP) ≤15 mmHg. Patients were divided to three tertiles based on their peak exercise PAWP. Mean age was 60 ± 20 years and 29% were males. Mean pulmonary arterial pressure was 31 ± 14 mmHg at rest and 42 ± 18 mmHg upon exercise. Mean change in PAWP between rest and exercise was 0.0 ± 4.3, 4.6 ± 2.4, and 16.6 ± 7.1 mmHg in the lower, middle, and upper tertiles, respectively (P < 0.001). Higher exercise PAWP tertiles were associated with reduced pulmonary vascular resistance (8.3 ± 6.7, 2.9 ± 2.7, and 5.8 ± 4.6 Woods units, respectively; P = 0.004). A multivariate linear regression model demonstrated that each 5 kg/m2 increase in body mass index was associated with 2.5 ± 1.0 mmHg increase in exercise PAWP (P = 0.017). A multivariate binary logistic model showed that subjects with borderline PAWP at rest (12–15 mmHg) were 4.5 times more likely to be in the upper tertile of exercise PAWP (P = 0.011). Conclusions In symptomatic patients with pulmonary hypertension, preserved left ventricular ejection fraction and PAWP ≤15 mmHg, exercise during right heart catheterization may unmask diastolic dysfunction. This is especially true for obese patients and patients with borderline resting PAWP.